The Significance of Islamic Spiritual Ethics in Human Personality Development - Ogunbado, Ahamad Faosiy; Ahmed, Umar; Daud, Balogun Adekunle (International Review of Management and Marketing, 2016)
In today's world, societies are experiencing rapid moral degeneration in all forms of indecencies which become unfortunately the main source of attraction. The animalistic features of human being are on top. Yet, holistic development of human personality is very crucial in Islam. Islam encourages all its adherents to live and behave based on Islamic ethical code of conducts. Indeed, Allah describes the Prophet (p.b.u.h) in al-Qur'an as the most exemplary character. This paper, therefore examines the significance of Islamic spiritual ethics in the development of human personality. On this basis, the study discusses intellectual, spiritual and physical aspects of human development as ways to improve on human personality. To achieve this objective, the study used document analysis which is an integral part of qualitative methodology. Qur'an and Hadith are taken as primary references while other Islamic literature materials are also taken into consideration. It is hoped that improve on Islamic spiritual ethics would significantly contribute to holistic development of human personality and thus improve morality in societies. Keywords: Significance, Islamic, Spiritual Ethics, Personality, Development. JEL Classifications: Z0, Z1, Z12